A Study to Assess the Effectiveness of Planned Teaching Program on Knowledge Regarding Electro Convulsive Therapy among Patient’s Relatives Undergoing ECT in Selected Hospitals in Vadodara - Kiran Patel; Seema Boresa; Mural Christian (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background of Study: Electroconvulsive therapy (ECT) is a safe and efficacious treatment; there is awidespread negative view of electroconvulsive therapy in public and professional circles. Clinical experienceand research have resulted in continued improvements to the efficacy and safety of electro convulsivetherapy. It is necessary to conduct research on this basis to modify the misconceptions and prejudices aboutthe electroconvulsive therapy1.Objectives: 1. To assesses the existing level of knowledge regarding electro convulsive therapy amongpatient’s relatives undergoing ECT.2. To determine the effectiveness of planned teaching on knowledgeregarding electro convulsive therapy among patient’s relatives undergoing ECT.3. To find out associationbetween pre test knowledge scores of patients relatives with their selected demographic variables.Methodology: Quantitative Research Approach was use with 2 Group pre test & Post test Design. Theinvestigator used pre-experimental one group pre-test post-test research design. Purposive samplingtechnique used for Selecting 30 Samples. The Structural questioners Used Check knowledge of ECT before& after administration of planned teaching program.Results: Analysis of paired t test is done to assess the effectiveness of planned teaching on knowledgeregarding electroconvulsive therapy. Researcher has found t value= 24.853 thus the obtained t value inthis study is more than the table value of t test at 0.05 level of significance. Hence the obtained t valueis significant. So it reveals that planned teaching on knowledge regarding electroconvulsive therapy isimproved in knowledge among patient’s relatives.